2019
DOI: 10.1523/jneurosci.0311-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Archaerhodopsin-3 Expression in Hypocretin/Orexin Neurons Engenders Cellular Dysfunction and Features of Type 2 Narcolepsy

Abstract: Narcolepsy, characterized by excessive daytime sleepiness, is associated with dysfunction of the hypothalamic hypocretin/orexin (Hcrt) system, either due to extensive loss of Hcrt cells (Type 1, NT1) or hypothesized Hcrt signaling impairment (Type 2, NT2). Accordingly, efforts to recapitulate narcolepsy-like symptoms in mice have involved ablating these cells or interrupting Hcrt signaling. Here, we describe orexin/Arch mice, in which a modified archaerhodopsin-3 gene was inserted downstream of the prepro-orex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Young-onset and adult-onset mice spent a similar amount of time in cataplexy and had a similar number of cataplexy bouts. At 3 weeks after DOX removal, the adult-onset group spent about 2% of the dark period (∼15 min) in cataplexy which is similar to prior descriptions of adult orexin-tTA; TetO DTA mice ( Tabuchi et al, 2014 ; Williams et al, 2019 ). However, Tabuchi et al (2014) reported that at 13 weeks after DOX removal, adult-onset mice spent about 8% (∼60 min) of the dark period in cataplexy ( Tabuchi et al, 2014 ).…”
Section: Discussionsupporting
confidence: 83%
“…Young-onset and adult-onset mice spent a similar amount of time in cataplexy and had a similar number of cataplexy bouts. At 3 weeks after DOX removal, the adult-onset group spent about 2% of the dark period (∼15 min) in cataplexy which is similar to prior descriptions of adult orexin-tTA; TetO DTA mice ( Tabuchi et al, 2014 ; Williams et al, 2019 ). However, Tabuchi et al (2014) reported that at 13 weeks after DOX removal, adult-onset mice spent about 8% (∼60 min) of the dark period in cataplexy ( Tabuchi et al, 2014 ).…”
Section: Discussionsupporting
confidence: 83%
“…Data from eArch3.0-expressing neurons could not be collected due to degradation in the quality of recordings or cells becoming highly depolarised (i.e. resting membrane potential > –50 mV) by the later stages of the protocol, suggesting that repeated eArch3.0 activation may alter electrical properties of neurons (Williams et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Diagnostic Classification Steering Committee., 1990;Burgess and Scammell, 2012). Optogenetic activation of orexin neurons induces wakefulness from sleep while optogenetic inhibition induces sleep from wakefulness (Adamantidis et al, 2007;Tsunematsu et al, 2011;Schone et al, 2012;Williams et al, 2019). Together, these studies indicate that orexin neurons play an important role in the maintenance of wakefulness and prevent cataplexy induced by positive emotions.…”
Section: Introductionmentioning
confidence: 94%